Open source Web applications for libraries - Coombs, Karen A. (Information Today, Inc., 2010)
"Interest in open source software has never been stronger, yet a general lack of information about specific tools and benefits-along with nagging concerns about dependability and support-has hampered adoption in libraries. In Open Source Web Applications for Libraries, authors Coombs and Hollister address these issues and provide librarians with guidance on a range of applications that can be used to improve reference services, instruction, and outreach to library users. In addition to explaining the use, installation, and configuration of such popular resources as Word Press, Drupal, Joomla, and Media Wiki, the authors cover library-specific open source applications such as SubjectsPlus, Blacklight, VuFind, and SOPAC. They compare and contrast the applications, describing key features, strengths, and weaknesses in order to help librarians make informed decisions. Numerous real-world examples illustrate how different types of libraries are using open source web applications today."--